Jurisprudential Analysis of Religious Court Decisions in Settling Waqf Property Disputes - Matondang, Ilhammuddin Arrasyid; Salma, Salma; Bahtiar, Bahtiar (jurnal.unprimdn.ac.id, 2026)
This study aims to analyze the judge's legal considerations in resolving waqf property disputes through Decision Number 3023/Pdt.G/2023/PA.Jr and Decision Number 60/Pdt.G/2021/PA.Sub. This study uses a normative legal research method with a descriptive analytical approach. Primary data sources were obtained from court decisions, while secondary data came from laws and regulations, books, journals, and other literature related to waqf and religious court law. Data collection techniques were carried out through library studies and documentation of relevant legal materials. The results of the study indicate that the judge's considerations in waqf dispute cases not only emphasize aspects of legal substance, but also pay attention to procedural legal procedures, particularly the implementation of mediation as regulated in PERMA Number 1 of 2016. In Decision Number 3023/Pdt.G/2023/PA.Jr, the panel of judges declared the lawsuit inadmissible because the plaintiffs were deemed not to have acted in good faith during the mediation process. Meanwhile, in Decision Number 60/Pdt.G/2021/PA.Sub, the judge emphasized that waqf disputes fall within the absolute jurisdiction of the Religious Courts, as stipulated in Law Number 3 of 2006 concerning Religious Courts. This research demonstrates that jurisprudence plays a crucial role in providing legal certainty, maintaining orderly waqf administration, and protecting the social function of waqf assets for the benefit of the community.